Video Games in Transmedia Storyworlds: The Witcher and the Mothership Problem - Joyce, Stephen (Imagining the Impossible: International Journal for the Fantastic in Contemporary Media, 2023)
This article looks at the impact of video games on transmedia fantasy worlds using The Witcher as a primary example. While Hollywood-centred franchises tends to follow a “mothership” model of transmedia, with one dominant platform surrounded by ancillary texts, The Witcher demonstrates an alternate model in which the video game series plays just as central a role as the TV adaptation. The article introduces the concept of “dual industrial core” transmedia to describe this type of franchise and explains its implications for fantastic storyworlds. Whereas mothership transmedia attempts to offer high levels of completeness and consistency, particularly in relation to the storyworld’s mythos and topos, dual industrial core transmedia favours greater flexibility. The key platforms for the storyworld maintain distinct differences between each other, often deliberately choosing to diverge in terms of character and storyworld representation, with the video game praised for its Slavic character while the TV series aims for a more generic fantasy environment reminiscent of Game of Thrones or The Lord of the Rings. What holds the fantasy world together is less a coherent mythos and topos than a particular kind of ethos, allowing creators in different media to expand the storyworld by creating “Witcher-esque” situations that are accepted as authentic if they remain true to the storyworld’s bleak, morally ambiguous worldview. As dual industrial core franchises become more common, we may also expect to see more fantastic storyworlds bound primarily by ethos with significantly less emphasis on a complete, consistent mythos and topos.